Giant Benign Struma Ovarii with High-Grade Fever, Elevated CA 125, and Hormonal Function in an Adolescent Patient - Ioana Anca Stefanopol; Alexandru Petecariu; Liliana Baroiu; Anca-Iulia Neagu; Roxana-Elena; Alexandru Nechifor; Diana-Andreea Ciortea; Nicolae Sarbu (MDPI AG, 2023)
Struma ovarii (SO) is a monodermal teratoma containing at least 50% thyroid tissue. Classically, SO is a hormonally inactive benign neoplasm that occurs in premenopausal women, and has unspecific clinical and imaging features. Its treatment is surgical and its diagnosis is established histopathologically. We report the case of a euthyroid 16-year-old girl presenting with abdominal girth increase. An abdomino-pelvic ultrasound showed a giant multicystic mass with transonic content and multiple septa, and magnetic resonance imaging suggested the diagnosis of right ovarian mucinous cystadenoma. Blood tests showed inflammatory syndrome, iron deficiency anemia, mild hepatocytolysis, and elevated serum CA 125 levels. High-grade fever occurred on the third day of hospitalization, but none of the preoperative tests could identify its origin. Cystectomy was performed, and the histopathological examination revealed benign SO with a few small cysts with purulent content. The patient developed hypothyroidism postoperatively. In conclusion, this case report reunites most of the uncommon features of SO and confirms the superiorityof histopathology in its definitive diagnosis, as well as the suitability of ovarian sparing techniques, as the best treatment option for cystic ovarian pathology in pediatric patients, even in cases of large tumoral size and elevated serum CA 125 levels.